Research advances in fungal polysaccharides: production, extraction, characterization, properties, and their multifaceted applications - Kumla, Jaturong; Thangrongthong, Suppasin; Kaewnunta, Atsadawut; Suwannarach, Nakarin (Frontiers in Cellular and Infection Microbiology, 2025)
Fungal polysaccharides have demonstrated significant biological potential, including immune stimulation, antioxidant activity, anticancer properties, and anti-inflammatory effects. These properties hold considerable promise for innovative applications across various fields. This study provides a brief review of current findings, based on literature published over the past 15 years on fungal polysaccharides. This includes the production process and various extraction methods, highlighting their distinct advantages and limitations. Additionally, we summarize techniques for purification and characterization, elucidating their biological properties and practical applications in medicine, pharmacology, the food industry, agriculture, and environment. Global patent trends related to fungal polysaccharides are also reviewed. Finally, we discuss challenges and future perspectives related fungal polysaccharides. This article offers valuable insights and enhances the understanding of fungal polysaccharides for researchers, paving the way for further research and applications.